Proses Kerja dan Strategi News Research and Development iNews dalam Mengevaluasi Program News untuk Menaikkan Rating dan Share - Rangga Permana; Dina Naifah (PT. RANESS MEDIA RANCAGE, 2024)
Private television stations have battled to air popular programs to boost ratings and share figures since their founding. Programs with high ratings and shares are popular with viewers. Indonesian news TV station iNews airs mostly news programs. As a private television company, iNews uses rating and share measures to determine audience approval of its shows. Therefore, a Research and Development team is needed to process rating and communicate data for program evaluation. This article seeks to (1) understand iNews News Research and Development and (2) Determine its strategy for sustaining or gaining ratings and shares. This article employs qualitative descriptive research method including observation, interviews, and documentation studies. The results demonstrate that the iNews research and development process used three stages, from gathering Nielsen rating and share data from the Ariana app to an agenda-setting editorial meeting. To maintain and/or enhance ratings and shares, iNews monitors and maps its and competitors' media according to its own ratings and shares. This helps define the agenda for the next week based on evaluations and conversations on essential and intriguing themes.